Competitiveness in the Southern Euro Area : France, Greece, Italy, Portugal, and Spain - Lissovolik, Bogdan (IMF Working Papers; Working Paper ;, 2008)
This collection of studies analyzes developments in nonprice external competitiveness of France, Greece, Italy, Portugal, and Spain. While France, Italy, and Portugal have experienced substantial export market share losses, Greece and Spain performed relatively well. Export market share losses appear associated with rigidities in resource allocation (sectoral, geographical, technological) relative to peers and lower productivity gains in high value-added sectors. Disaggregated analysis of goods and services export markets provides insights on aspects such as quality, market concentration, growth of destination markets, and geographical and sectoral diversification. Also, increased import penetration, offshoring and FDI could improve productivity and export performance.